Scalable video streaming over overlay/underlay cognitive radio network. - Abdul Karim, Hazerul; Mohamad, Hafizal; Ramli, Nordin; Sali, Aduwati (2012)
Cognitive radio (CR) with dynamic spectrum allocation (DSA) allows new or secondary devices to opportunistically access a portion of spectrum, which belongs to primary (licensed) users (PU). This allows the secondary users (SU) to transmit data services when the PUs are not using the spectrum. However, problem arises when SU experiences interrupted services if the PU needs to use the spectrum. The objective of this paper is to provide uninterrupted multimedia data services (video transmission) to SU by allowing the SU to receive data in both the overlay and underlay mode of CR. Since the underlay mode CR is characterized by low power and low data rate, base layer video streaming of a scalable video coding (SVC) is an attractive solution. In overlay mode, the enhancement layers and the base layer of the SVC are streamed without interruptions. The base layer video is protected from video packet loss by using I-frames insertion. Simulation results show that it is a great challenge to transmit video in the underlay CR. Nevertheless, with high protection of the base layer video of the SVC, acceptable video quality can be achieved.